Cost Control and Profitability of Selected Manufacturing Companies in Nigeria - Godwin Emmanuel Oyedokun; Amos Olafusi TOMOMEWO; Sunday Ajao OWOLABI (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
Profitability in manufacturing companies in Nigeria depends on the ability of the companies to grow their earnings and tame their cost profile through cost control techniques. Many manufacturing companies seem not to understand these costs and the impact they have on profitability. This study examined the effect of cost control on the profitability of selected manufacturing companies in Nigeria. The population of the study was the 78 manufacturing companies listed on the Nigeria Stock Exchange as at 31st December 2017. A sample frame of 23 companies listed on the consumer goods sector was selected out of which five companies were considered for a period of 10 years (2005 – 2017). The study adopted a judgmental sampling technique. Data were obtained from the audited financial statement, and the accounts have already validated by regulatory authorities. The study took descriptive and inferential (regression) statistics. It was found that there is a significant negative relationship between the cost of raw materials (CoRM) and profit before tax of manufacturing companies in Nigeria. The study concluded that cost control has a significant positive effect on the profitability of manufacturing companies in Nigeria for the period under review. Therefore, it is recommended adequate management and alternative sourcing of raw materials.